Modern ideas about pharmacotherapy of pelvic congestion syndrome in women - R. V. Akhmetzianov; R. A. Bredikhin (Амбулаторная хирургия)
Pelvic congestion syndrome (PCS) is not a rare and poorly studied disease. However, the current state of PCS pharmacotherapy is characterized not only by insufficient study of this issue, but also by the presence of conflicting views. The results of key publications prove that the main trend in PCS treatment is associated with invasive methods. At the same time, pharmacotherapy is a successful solution leading to the relief of the main symptoms in most patients with PCS. The current review is based on the analysis of data from known scientific literature and clinical guidelines. It covers various aspects of conservative treatment of patients with PCS and focuses on pharmacotherapy. This publication aims to summarize the known data related to drug correction of PCS, based on evidence-based medicine. The review presents information related to the history of the selection of pharmacotherapy, including combinations of drugs of various groups with the appointment of analgesics, hormonal, psychotropic, venoactive drugs and selective vasoconstrictors. An objective analysis of each of the indicated pharmacological groups of drugs is presented with an assessment of subsequent prospects, including not only known therapeutic agents, but also those not previously used in the therapy of PCS. The drug of choice in the arsenal of the attending physician are vasoactive drugs based on diosmin with the largest evidence base in MPFF. In the presence of severe pain syndrome, short-term administration of analgesics is advisable. The presence of anxiety-depressive disorders, as well as severe CPP, can serve as an indication for taking psychotropic drugs. Further research is needed to expand the potential of pharmacotherapy for patients with PCS.